Alternative Approaches to Analyzing Markets with Asymmetric Information: Reply - Stiglitz, Joseph E.; Weiss, Andrew (American Economic Review, 1983)
Stiglitz and Weiss discuss alternative approaches to analyzing markets with asymmetric information.